Battery Charging Station for E-Bike Powered by A Vertical-Axis Wind Turbine - Solaisamy, Dr. Divya; J , Dr. Babitha Thangamalar; S , Dr. Muthkrishnan; S , Dr. Ramani (International Journal of Basic and Applied Sciences, 2025)
Nowadays, Electric Vehicles (EVs) are highly used due to increasing air pollution. In ‎India, there are about 1742 EV charging stations, but EV sales are moderate due to the long ‎charging time of EV batteries. To minimize the charging time, much research is underway. ‎In order to solve that problem, part of the solution is Battery Swapping Stations (BSSs). ‎Unfortunately, BSSs have many disadvantages. The proposed model of charging station is ‎explained by the wind stand-alone partially discharged battery charging station, and it is being ‎planned for the campus of the Coimbatore Institute of Technology (CIT), Coimbatore. Taking ‎into account the available student and faculty time and wind power generation, this electric ‎charging station has been designed. At night on CIT’s campus, there is a high wind speed ‎compared to the daytime, which occurs while the backup battery is charging. The backup ‎battery keeps the system functioning. In the proposed system, a fuzzy logic controller is used ‎to verify the operation of the charging station‎.